Central pseudorapidity gaps in events with a leading antiproton at the fermilab tevatron pp collider. - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2003)
We report a measurement of the fraction of events with a large pseudorapidity gap deltaeta within the pseudorapidity region available to the proton dissociation products X in p+p-->p+X. For a final state p of fractional momentum loss xi(p) and 4-momentum transfer squared t(p) within 0.06<xi(p)<0.09 [0.2]="" [630]="" and="" at="" deltaeta="" events="" fraction="" gev,="" gev2="" of="" sqrt[s]="1800" the="" with="" |t(p)|<1.0="">3 is found to be 0.246+/-0.001 (stat)+/-0.042 (syst) [0.184+/-0.001 (stat)+/-0.043 (syst)]. Our results are compared with gap fractions measured in minimum bias pp collisions and with theoretical expectations.</xi(p)<0.09>